Acute Toxicity of Leaf Extracts of Enydra fluctuans Lour in Zebrafish (Danio rerio Hamilton). (25th April 2020) - Xavier, Jobi; Kripasana, Kshetrimayum
Abstract : The present study was focused on the concentration-dependent changes in oral acute toxicity of leaf extracts of E . fluctuans in zebrafish. The study was also aimed at the details of histopathological changes in the gill, liver, brain, and intestine of zebrafish exposed to the leaf extracts of the plant E . fluctuans . Enydra fluctuans Lour is an edible semiaquatic herbaceous plant used widely for the alleviation of the different diseases. Since there were no toxicity studies conducted on this plant, the present study was an attempt to look into the elements of toxicity of the plants. Two types of experiments are conducted in the present study. First, the acute oral toxicity study was conducted as per the OECD guidelines 203. Second, histopathological changes were observed in the fishes exposed to the lethal concentrations of plant extract. The oral acute toxicity studies conducted on Zebrafish have revealed that the leave extracts of E . fluctuans were toxic to the tested fish at the concentration of 200 mg/kg body weight. The histopathological studies conducted on the intestine of treated fishes showed that treatment has induced rupturing of the villi structure and fusion of villi the membrane and detachment of the villi structure from the basal membrane of the intestine. The histology of the liver also showed severe vacuolization in the cells while it is not affected in control. The studies on gills showed the detachment of the basal epithelial membrane in the gills compared to control which might have led to death of the fish. The histopathological observations of brain tissues treated with test samples also revealed the marked impingement in the brain parenchyma while the control is normal without impingement of the brain.